Effects on Aortoiliac Fluid Dynamics After Endovascular Sealing of Abdominal Aneurysms - Casciaro, Mariano Ezequiel (2018)
Objectives: To evaluate the effects on aortoiliac fluid dynamics after the implantation of an endograft based on endovascular aneurysm sealing (EVAS) versus endovascular aneurysm repair (EVAR) strategy. Methods: An adaptive geometrical deformable model was used for aortic lumen segmentation in 8 patients before and after the surgery. Abdominal aneurysms were treated with an endograft based on the EVAS system (Nellix, n = 4) and with a device based on an anatomical fixation technology (n = 4). Pressure, blood velocity, and wall shear stress (WSS) were estimated at different aortic regions using computational fluid dynamics methods. Physiologic inlet/outlet flow values at the abdominal aorta, the celiac trunk, and the mesenteric and the renal arteries were set. Pressure references were set at iliac arteries outlet. Results: Maximum aneurysm sizes were similar for both groups in the preoperative scans. The lumen area was lower after EVAR (P <.05) and EVAS (P <.01) compared to preoperative aortic lumen sizes. Pressure increase was higher in the proximal abdominal aorta after EVAS compared to EVAR (2.3 ± 0.3 mm Hg vs 0.9 ± 0.3 mm Hg, P <.001). Peak blood velocities inside the endografts were 3-fold higher for EVAS compared to EVAR (54 ± 5 cm/s vs 17 ± 4 cm/s, P <.01). Velocities at the iliac arteries also remained higher for EVAS (38 ± 4 cm/s vs 24 ± 4 cm/s, P <.05). Peak WSS at the iliac arteries remained higher for EVAS compared to EVAR group (P <.05). Conclusion: The significant modification of the aortic bifurcation anatomy after EVAS alters aortoiliac fluid dynamics, showing a pressure impact at the renal arteries level and an acceleration of the blood velocity at the iliac region with a concomitant increase in peak WSS.